PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERBANKAN (Studi Kasus Pada Bank Pembangunan Daerah di Indonesia Periode 2010-2013) - Ken Hutami, Tyas Rukmi; Marsono, Marsono (Diponegoro Journal of Accounting, 2015)
This study aims to analyze the factors of corporate governance mechanism that affect the corporate financial performance in Regional Development  Bank (BPD). Independent variables used in this study are board of commissioner, board of director, audit comitte, risk comitte, audit quality, blockholder ownership and whistleblowing system. Size is used as a control variable. The method used to determine the sample was purposive sampling, which of these methods obtained a sample of 80 Regional Development Bank. The results indicate that some determinant of corporate covernance such as board of commissioner (CAR), blockholder ownership (NIM & LDR) and whistleblowing system (LDR) affect the financial performance of Regional Development  Bank (BPD). However, other factors, such as board of commissioner (NIM & LDR), board of director, audit comitte, risk comitte, audit quality, blockholder ownership (CAR) and whistleblowing system (CAR & NIM) do not explain the financial performance of Regional Development  Bank (BPD).